2020
DOI: 10.1039/c9nj05226g
|View full text |Cite
|
Sign up to set email alerts
|

A simple D–π–A system of phenanthroimidazole-π-fluorenone for highly efficient non-doped bipolar AIE luminogens: synthesis, and molecular optical, thermal and electrochemical properties

Abstract: We report the synthesis of phenanthroimidazole based dyes incorporating fluorenone using Suzuki coupling and their aggregation induced emission characterisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The solution-processed bottom gate–top contact organic field-effect transistors (OFETs) showed an excellent hole mobility of 0.70 cm 2 /V·s with an on/off ratio of 10 7 . Considering all of the above points, we envisaged the synthesis of a new class of self-assembling organic semiconductors comprising a tetrasubstituted imidazole moiety bearing two di-alkoxy phenyl units as electron donors (D), central naphthalene/perylene bisimide moieties as acceptor (A) units, and phenyl moieties as π-bridges between the D and A units . The structures of the final target molecules based on the proposed donor−π–acceptor−π–donor (D 2 –π 2 –A) architecture are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…The solution-processed bottom gate–top contact organic field-effect transistors (OFETs) showed an excellent hole mobility of 0.70 cm 2 /V·s with an on/off ratio of 10 7 . Considering all of the above points, we envisaged the synthesis of a new class of self-assembling organic semiconductors comprising a tetrasubstituted imidazole moiety bearing two di-alkoxy phenyl units as electron donors (D), central naphthalene/perylene bisimide moieties as acceptor (A) units, and phenyl moieties as π-bridges between the D and A units . The structures of the final target molecules based on the proposed donor−π–acceptor−π–donor (D 2 –π 2 –A) architecture are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The scientists found that through the HOMO-LUMO design of the D-π-A structure, the ISC can be tuned such that the energy gap between the triplet state (T1) and the singlet state (S1) is small. [17][18][19][20] Unfortunately, molecular photosensitizers are often unstable and hydrophobic in aqueous solution, which may limit their applications. 21,22 To address these issues, various nanoparticle platforms have been developed, such as liposomes, silica, metals, and bovine serum albumin nanoparticles.…”
Section: Introductionmentioning
confidence: 99%